Pelatihan Penguatan Literasi dan Numerasi Dalam Implementasinya Mendukung Merdeka Belajar Bagi Guru Sekolah Dasar di Provinsi Lampung - Dina Maulina; Viyanti; Hermi Yanzi; Ismi Rakhmawati (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS LAMPUNG, 2022)
Teachers are the spearhead in determining the quality of education. 21st Century Education will produce human beings who are intelligent and competitive with competence to develop themselves in the diverse situation and condition. Therefore, it is necessary to have a coaching program for teachers by involving educational institution in building literacy and numeracy strengthening by implementing responsibility that targets on the improvement of the competence and skills of elementary school teachers. Similarly, it requires full support from government programs that are carried out consistently. The implementation of free learning promoted by the government is an absolute requirement for every elementary school. The implementation of this service activity is planned through 5 stages of activity, namely (1) preparation, (2) training and workshops for strengthening literacy and numeracy which will be carried out offline by complying with health protocols; 3) assistance on collaborative projects to strengthen literacy and numeracy; 4) online sharing session regarding the implementation of literacy and numeracy strengthening for students, and (5) Reporting. The implementation of training activities succeeded in increasing the competence of elementary school teachers regarding knowledge of implementing independent curriculum learning in the high category (n-gain = 0.95). This activity produces learning products in the form of lesson plans, worksheets, evaluation materials based on literacy and numeracy by inserting an understanding of the Pancasila youth profile.